STUDI PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) TEMA PEDULI TERHADAP MAKHLUK HIDUP KELAS IV DALAM KAITAN DENGAN IMPLEMENTASI KURIKULUM 2013 - Purnama, Wawan Mulyadi (al-Hikmah : Jurnal Studi Islam, 2020)
The aim of the study is to produce lesson plans in the theme of â€œpeduli terhadap makhluk hidupâ€ of thematic integrated learning with scientific approach in order to implemented the curriculum of 2013 through prototype development process, idea description of try out result and examine the effectiveness of the lesson plans through restricted test. To attain these aims, then the 4-D (define, design, develop, and disseminate) model is used for the development phase. Then, this study was done for the develop phase only. The data were collected by using APRP instrument, APPP and teacher pedagogic perception. The design of lesson plan is validated by experts and  practitioners, then the lesson plan was examined through restricted test for the elementary school in Labuhan Haji Subdistrict which consisted of 6 clasess. Descriptive statistic was administered to analyze the data of the study. The result indicates that: (1) experts validation and lesson plansâ€™ practitioners acquired 0,83, categorized as proper without revision (2) the average of lesson plan implementation was 91,98 and categorized as excellent (3)Teachersâ€™ comprehension toward the philosophy of integrated learning based on the work period showed the average 82,67 and categorized as adequate. Then, there was a strong relation between teachersâ€™ comprehension and work period that was proved by the result of analysis using Chi quadrate and Contigency Correlation (CC)